2022
DOI: 10.3389/feduc.2022.871036
|View full text |Cite
|
Sign up to set email alerts
|

Strengths and Weaknesses of Emergency Remote Teaching in Higher Education From the Students’ Perspective: The Portuguese Case

Abstract: Motivated by the COVID-19 pandemic, most students of higher education institutions (HEIs) in Portugal experienced online learning from March 2020 to July 2020. Based on the answers obtained from students to a set of two open questions included in a questionnaire, this article aims to identify the positive (strengths) and negative (weaknesses) aspects of online learning during this period, which is also known as emergency remote teaching (ERT). A total of 2,107 valid answers were gathered. Issues related to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The study's participants found evidence of the COVID-19 pandemic's effects on various aspects of students' learning, including class projects, assignment loads, learning quality, motivation for learning, educational activities, goals, subject knowledge, learning performance, educational opportunities, and the length of their studies. This outcome corroborates the findings of previous research [5,87]. The effects of anxiety on many pupils' learning and academic performance have been detrimental.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The study's participants found evidence of the COVID-19 pandemic's effects on various aspects of students' learning, including class projects, assignment loads, learning quality, motivation for learning, educational activities, goals, subject knowledge, learning performance, educational opportunities, and the length of their studies. This outcome corroborates the findings of previous research [5,87]. The effects of anxiety on many pupils' learning and academic performance have been detrimental.…”
Section: Discussionsupporting
confidence: 91%
“…It argues that when students have a positive growth opportunity, they produce meaning, which leads to changes in their attitudes, behaviors, and perception. As students undergo mindset changes, they should be given challenging tasks that require them to think critically and rationally to evaluate their understanding of what is happening [5,12,13]. Moor [64] also stated that transformative learning occurs when learners interact with their surroundings and integrate with the learning process.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations